Optimization Design of the Second-phase Cofferdam Demolition of Datengxia Water Conservancy Project - CHEN Guihua; LI Guangyi; SU Wenliang (Renmin Zhujiang)
The second-phase cofferdam demolition of the Datengxia Water Conservancy Project has large quantities,a tight construction period,and great difficulty.To optimize the demolition design,this paper optimizes the demolition range and elevation of upstream and downstream transverse cofferdams and longitudinal cofferdams by a 1∶80 overall model test,which is combined with factors such as relevant hydraulic conditions,energy dissipation and erosion prevention,investment,and construction period.After optimization,the right bank side of the upstream transverse cofferdam is demolished to the elevation of 31.17 m and the sluice gate section is the elevation of 25 m.The demolition length of the upstream section of the longitudinal cofferdam is 275 m,and it is demolished to the elevation of 36 m with the remaining 50 m not being demolished.The downstream horizontal earth-rock cofferdam is completely demolished,and the longitudinal cofferdam is demolished to the elevation of 30 m,with a demolition length of 202 m.The optimized demolition scheme meets the designed hydraulic conditions,reduces the construction difficulty,and decreases the demolition quantities and investment.